(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
With its good biocompatibility and excellent mechanical properties, silk fibroin microneedles can transport drugs to the body fluid circulation system and then act on the affected area, so as to replace intravenous injection and oral administration, and achieve the purpose of treating diseases. In the process of processing and use, silk fibroin microneedles are non-toxic, harmless, pollution-free and biodegradable to human body and environment. Therefore, the application prospect and application range of silk fibroin microneedles are very wide. In this paper, the effects of proline and its derivatives prolinamide and hydroxyproline on the performance of silk fibroin microneedles were studied on the basis of the previous experiments of constructing microneedles to carry drugs. The composite silk fibroin microneedles were obtained by pouring the amino acid/silk fibroin mass ratio of 0/10, 1/10, 2/10, 3/10 and 4/10 into a polydimethylsiloxane mold, after vacuum defoaming and drying. The length of the microneedles was about 600 μm. The aggregation structure of amino acid/silk fibroin microneedles was measured by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Raman Scattering Spectroscopy. The mechanical properties of the microneedles were measured by texture analyzer. The results showed that: (1) The silk fibroin microneedles prepared by adding proline and its derivatives had predominately Silk I crystal structure; (2) When the mass ratio of proline and its derivatives to silk fibroin reached 2/10, it had a higher swelling degree and a lower dissolution rate; (3) The silk fibroin microneedles prepared by proline and its derivatives have good mechanical properties. The following conclusion was drawn: with the addition of proline and its derivatives, silk fibroin microneedles with higher swelling degree and lower dissolution rate can be obtained. The crystal structure of Silk I is formed inside the microneedles, which has good penetration and fracture properties. It is expected that the microneedles can be used as swelling microneedles for drug transdermal delivery.